Recent Trends in Humanities, Literature, Sociology and Psychology - Pooja Midha; Usha Vaidya; Dhanbanti Chanchal (AG Volumes, 2022)
The act of passing on ideas or information from one person to another is known as communication. When we express our thoughts in a concise and understandable manner, we are engaging in effective communication. One person is the transmitter and another is the receiver in a two-way exchange of messages. The ability to communicate effectively is critical to a company’s success. A company cannot function well if it is unable to communicate with its customers, employees, and/or other companies. Customers are more likely to trust a company if they know what they’re getting into. It fosters a close working connection between management and employees. An organization’s ability to function and flourish depends on its ability to communicate effectively. Most businesses depend on excellent communication with both consumers and staff in order to increase sales and expand the company. Unwanted business outcomes are often the consequence of a company’s management team’s failure to communicate effectively or efficiently.